Brewery Spent Grain: Chemical Characteristics and utilization as an Enzyme Substrate - K.M, Khidzir; Abdullah, Noorlidah; P., Agamuthu (Malaysian Journal of Science, 2010)
Grains in a brewery that have been removed of their sugar content is classified as a byproduct known as spent grain. It is a low-cost material and is available year-round. In Malaysia, approximately 15% of brewery spent grain (BSG) that is produced is salvaged and sold as feedstock supplement, while the remainder is discarded in landfills. This is a waste of a potentially useful resource. The chemical composition of fresh BSG was studied. Nine species of fungi were individually inoculated onto sterile BSG and solid state fermentation occurred without chemical adjustment or supplementation. Activity of laccase, lignin peroxidase, xylanase, amylase, carboxymethyl cellulase, protease and tannase was assayed. BSG consists of lignin and cellulose. High enzyme activity of laccase was shown by Pleurotus sajor-caju, Penicillium chrysogenum, and Aspergillus niger. This study is possibly the first to report laccase activity by solid state fermentation of spent grain.